Profitability analysis of cut flower cultivation in Bangladesh: Constraints and opportunities - Kaysar, Md Imrul; Islam, Md Shofiqul; Hoq, Mohammad Shamsul; Mukta, Sultana Parvin; Kausar, A K M Golam (International Journal of Agricultural Research, Innovation and Technology, 2024)
Bangladesh has immense potential for cut flower production and export to the world market. Although the export earnings from cut flower cultivation are gradually increasing in our country, production and profitability are hindered by some constraints. The present study was undertaken in Jashore (Jhikargachha) and Dhaka (Savar) districts to examine the financial profitability, constraints, and opportunities of cut-flower cultivation in Bangladesh. A total of 120 cut flower cultivating farmers were selected for interview in 2019, taking 60 sample farmers from each location. Multi-stage random sampling method was followed to collect primary data. For profitability analysis, two cut flowers, namely gladiolus and rose, were selected for the study. The result indicates that per hectare total cost, net return, and benefit-cost ratio (BCR) were Tk. 687439, Tk. 261509 and 1.38, respectively, for gladiolus cultivation. On the other hand, net present value (NPV), internal rate of return (IRR), and BCR of rose cultivation were Tk. 2325762, 146%, and 1.46, respectively, indicating that rose production is highly profitable to the farmers of the study areas. Despite such potentialities, cut flower cultivation was constrained by the requirement of high initial investment, lack of modern varieties, lack of credit facility, lack of storage facility, attack by pests & diseases, and uncertain market price. However, there is a huge scope to increase cut flower production by removing constraints in Bangladesh that can boost up livelihoods, incomes, and living conditions of rural people. Int. J. Agril. Res. Innov. Tech. 13(2): 41-48, Dec 2023